Frequency of high risk behaviour in patients with alcohol dependence syndrome: a cross sectional study - Melrine Carl, Ashwitha; A. T., Safeekh (International Journal Of Community Medicine And Public Health, 2023)
Background: Alcohol use and high-risk behaviour has been shown to have an association. Severity of alcohol dependence has an association with frequency of risk-taking behaviour. Objectives were to evaluate the frequency of high risk behaviour in alcohol dependence syndrome and to find any correlation between psychosocial variables and high risk behaviour. Methods: 100 individuals with ICD 10 diagnosis of alcohol dependence syndrome were studied using semi structured interview. High risk behaviour was assessed using violent risk appraisal guide and deliberate self-harm inventory. The age of onset of initiation of alcohol use and dependence and severity of alcohol dependence syndrome were assessed and analyzed by frequency and Chi square test. Results: In 100 subjects with alcohol dependence syndrome, 4 (17.4%) and 7 (30.4%) of subjects with severe dependence had road traffic accidents and risky sexual and violent behaviour respectively. There was a statistically significant association between age of onset, age of dependence and high-risk behaviour. Conclusions: The present study concluded that most individuals with alcohol dependence syndrome had high risk behaviour. Road traffic accident was the most common followed by risky sexual and violent behaviour. There was a significant association between severity of alcohol dependence and high risk behaviour.